Pharmaceutical Care Model and Implementation in Clinical Pharmacy Services: A Qualitative-Descriptive Literature Review - Cinthya Yuniar (Sciences and Clinical Pharmacy Research Journal, 2026)
This article aims to describe and analyze the development, implementation, and challenges of pharmaceutical care–based models in clinical pharmacy services, with emphasis on their contribution to patient-centered care and improved therapeutic outcomes. A qualitative descriptive design using a library research approach was employed, with data collected through systematic searches of peer-reviewed articles, official reports, and relevant policy documents published between 2015 and 2025 focusing on pharmaceutical care models, clinical pharmacy practice, and interprofessional collaboration. A total of 18 eligible studies were analyzed inductively using thematic analysis involving data reduction, categorization, and synthesis. The findings reveal a clear paradigm shift from product-oriented dispensing toward comprehensive patient-centered pharmaceutical care, with 72% of studies reporting increased pharmacist involvement in medication review, therapy monitoring, and identification of drug-related problems, while 67% highlighted improvements in patient counseling and medication adherence. Furthermore, 61% of the studies documented reductions in medication errors or drug-related problems following implementation. Improved clinical outcomes were reported in more than half of the studies (56%), particularly among patients with chronic diseases and high-risk conditions in settings with strong interprofessional collaboration. However, nearly 70% of the studies identified persistent barriers, including limited human resources, inadequate documentation systems, uneven interprofessional collaboration, and insufficient regulatory or infrastructural support, especially in low- and middle-income settings. Overall, pharmaceutical care–based models significantly contribute to advancing clinical pharmacy practice and inform future policy, education, and research.